SISTEM INFORMASI PROMOSI TEMPAT WISATA BERBASIS WEB - Pora Ina, Anjelina; Elefri Neno, Friden; Ema Ose Sanga, Felysistas (JATI (Jurnal Mahasiswa Teknik Informatika), 2024)
Sophisticated and rapidly developing technology is a necessity for making computerised information systems used to create information systems that are better efficiency and accuracy than manual information systems. Southwest Sumba Regency has many tourist attractions but few people know about them because of limited access to information. Web information systems are very important for storing information. people who want to know tourist attractions without the need to visit them go to the location to be visited first Southwest Sumba Regency is one of the areas that has the beauty of natural tourism which is very attractive to foreign and local tourists. With this information system, it will be easier for users for local or foreign tourists to access information about the location of tourist attractions in the Southwest Sumba Regency area. In this research study, the design of a tourist attraction introduction information system with PHP and MySQL programming languages, the technique used is a waterfall process that starts from the analysis of the analysis.is a waterfall process that starts from needs analysis, system design, and coding of programmes, testing programmes, and system implementation.programme, testing programme, and system implementation. Information about tourism destinations in a system. Southwest Sumba Regency provides an explanation to residents about the information. location of the place along with the facilities that support it. The information available on this website includes knowledge about tourist attractions. Translated with www.DeepL.com/Translator (free version)